ABAQUS plug-in finite element tool for designing and analyzing lattice cell structures. (July 2022) - Fadeel, Abdalsalam; Abdulhadi, Hasanain; Srinivasan, Raghavan; Mian, Ahsan
Highlights: A Plug-in tool named lattice structure designer (LSD) has been developed for periodic lattice cell structures to work with ABAQUS finite element software. This tool was developed via ABAQUS graphical user interface (GUI) based on python code. The LSD tool works for three lattice families: BCC, pyramidal and tetrahedron configurations. The tool can be further updated to add any other periodic lattice structures. The tool has capability of applying boundary conditions and compression load been used to simulate the axial compression behavior of the adopted lattices. Abstract: This paper presents the development of a lattice structure design (LSD) tool for building and analyzing different configurations of 3D-printed lattice structure (LS). This tool was developed via ABAQUS graphical user interface (GUI) based on Python code. Due to the extensive research activities in the field of lattice design using experimental and computational methods, there is a high demand for finding new techniques to reduce the computational time and human effort. Also, several challenges were revealed while creating finite element models for lattices of complicated geometries. These models showed the capability for capturing the elastic and inelastic mechanical responses of LSs during the compression test. Consequently, the LSD tool was designed not only to build lattice structures in a short time and simple way, but also to analyze the associated compressive mechanical behavior that goes beyond initial yielding to cover the entire crushing behavior. This paper examined many challenges involved in generating and decomposing the lattice geometry, creating hexahedron elements and optimizing the mesh density, assigning and inserting the material type, activating the face recognition to define the boundary and loading conditions, and conducting linear and polar patterns. Finally, to demonstrate the effectiveness of the new approach in designing and analyzing LSs, finite element results were validated with the previous experimental findings.